Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I recently came across two properties that imply that a group is abelian:

  • If the order of each element except the identity element of a group is two then the group is abelian.
  • If every element of the group is its inverse then the group is abelian.

Obviously this comes from my module with no proof but I also looked in my book and found none of this there either, so I am interested in knowing how we can prove it?


share|cite|improve this question
These are not properties of abelian groups, but properties which are sufficient to have an abelian group. They are not necessary. – Raskolnikov Feb 12 '11 at 12:58
@Raskolnikov:So if any of this properties holds then the group is abelian under any binary composition? – Quixotic Feb 12 '11 at 13:00
@Debanjan: are you really asking whether in all abelian groups the order of every element is 2? – lhf Feb 12 '11 at 13:10
For both: write $1 = (ab)(ab)$ and multiply with $ba$ from the right or left, as you prefer. – t.b. Feb 12 '11 at 13:14
It's funny if you write it like this: $ab = a(ab)(ab)b = (aa)ba(bb) = ba$. – Myself Feb 12 '11 at 20:23
up vote 3 down vote accepted

In fact, the following is a stronger condition:

Prop. Let $G$ be a group, and let $x$ and $y$ be elements of $G$. If $$(xy)^2 = x^2y^2$$ then $x$ commutes with $y$; that is, $xy=yx$.

If every element of the group has order dividing $2$, then both sides of the equation above are equal to $1$, so the equality holds for any two elements of $G$; if every element is its own inverse, then every element has order $1$ or $2$, then again both sides equal the identity, so the result follows for every pair of elements. If any pair of elements commute, then the group is abelian.

This is a stronger result, though, because it also applies in other cases, when neither side is the identity but they are nonetheless equal.

Proof. Write the equation explicitly as $$xyxy = xxyy.$$ Multiplying on the left by $x^{-1}$ and on the right by $y^{-1}$, We get $$x^{-1}xyxyy^{-1} = x^{-1}xxyyy^{-1}$$ which is the same as $$yx = xy.$$ So $x$ and $y$ commute. $\Box$

Now, try proving the following:

Proposition. Let $G$ be a group, and let $x$ and $y$ be two elements of $G$. The following are equivalent (that is, if one of them holds, then they all hold; if any on of them is false, then they are all false):

  1. $xy=yx$.
  2. $(xy)^2 = x^2y^2$.
  3. $(xy)^{-1} = x^{-1}y^{-1}$.
  4. There exists an integer $n$ such that $$(xy)^{n+i} = x^{n+i}y^{n+i}$$ holds for $i=0,1,2$.
share|cite|improve this answer

Suppose $x^2=1$ for all $x$ in the group. This is equivalent to $x=x^{-1}$ for all $x$. Now consider $x=ab$.

share|cite|improve this answer

By converse I assume you mean

$G$ abelian $\Rightarrow$ the order of $g \in G$ is two


Let $G$ be $\mathbb{Z} / 3 \mathbb{Z}$ with addition mod 3, i.e. $G = \{ 0, 1, 2\}$. This group is clearly abelian but $1 + 1 \neq 0$, so the order of $1$ is not $2$, so the converse doesn't hold.

I assume you are aware that both statements you gave are equivalent.

Here is a proof of the claim:

claim: $\forall g \in G: \hspace{3mm} gg = e \hspace{3mm}$ then $G$ is abelian


Let $a$,$b$ $\in G$. Then $a = a ^{-1}$ and $b = b^{-1}$. Let $e$ be the neutral element of $G$. We want to show

$$ ab = ba$$

Because $G$ is a group we know if $a,b \in G$ then $ ab \in G$ and by assumption $abab = e$. But

$$ e = abab = ab a^{-1}b^{-1} = ab (ba)^{-1}$$

Multiplying both sides with $ba$ yields

$$ ba = ab$$

Note that I have used $(ab)^{-1} = b^{-1}a^{-1}$ which holds for any group and you have to prove as well.

share|cite|improve this answer

Look at this if it helps:

  • Since all your elements are of order $2$ you have $x^{2}=e$ for all $x \in G$ which implies $x=x^{-1}$. If you have two elements $a,b \in G$, then by above you have $a \cdot b = a^{-1} \cdot b^{-1}=(ba)^{-1}=ba$. Hence your group is abelian.

  • You have $x =x^{-1}$ for all $x \in G$. Continue doing as I proceeded for the first one. You should be able to get it.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.